Implementing AML/CFT Measures in the Precious Minerals Sector : Preventing Crime While Increasing Revenue - Mathias, Emmanuel (Technical Notes and Manuals; Technical Notes and Manuals ;, 2014)
The trade in precious metals and stones has been linked to illicit financial flows, corruption, smuggling, drug trafficking, illicit arms trafficking, and the financing of terrorism. In addition, the extraction of precious minerals and the subsequent trade in these resources, if properly managed, present significant revenue opportunities, particularly for countries facing development needs. Building on staff expertise in anti-money laundering and combating the financing of terrorism (AML/CFT) and technical support and analytical advice on the management of natural resources, this note is a reference guide to aid countries in using the AML/CFT framework to help combat crime related to and affecting the precious minerals sector while raising revenue.